Customer behavioral intention: Influence of service delivery failures and perceived values in Malay restaurants / Zulhan Othman, Salleh Mohd Radzi and Mohd Hafiz Mohd Hanafiah - Othman, Zulhan; Mohd Radzi, Salleh; Mohd Hanafiah, Mohd Hafiz (UiTM Press, 2014)
Undeniable that to be successful, restaurant industry must have the ability to deliver satisfying experiences to customers. Most successful restaurants compete on the basis of their ability to delivery superior and unexceptional service. Nevertheless, even in the luxurious restaurant with the best customer-oriented strategic plans, immaculate service delivery cannot be assured. Service delivery failures, in fact, can make restaurants out of business by neglecting the cause of failure. Apart from that, it is contended that customers who had a bad experience will still revisit and remain loyal to the restaurants that have positive perceived values. Thus, this study empirically investigates the influence of service delivery failures, perceived values and customer behavioral intention in Malay restaurants. It is structured according to a quantitative investigation among restaurant customers who had visited and experienced service delivery failures when dining at pre-identified Malay restaurants in Klang Valley.